Baclofen did not modify sexually dimorphic c-Fos expression during morphine withdrawal syndrome - Pedrón, Valeria Teresa (2013)
In previous studies, we have reported sex-related differences during morphine withdrawal. We have also shown that the GABAB agonist baclofen (BAC) was able to prevent the morphine withdrawal syndrome in male as well as in female mice. Considering that early gene expression is induced by drugs of abuse, we evaluated the expression of c-Fos in several brain areas, in mice of either sex during naloxone (NAL)-precipitated withdrawal, and after pretreatment with BAC. Swiss-Webster prepubertal mice were rendered dependent by i.p. injection of morphine (2 mg/kg), twice daily for 9 days. On the 10th day, dependent mice were divided into two groups: the withdrawal group received NAL (6 mg/kg, i.p.) after the last dose of morphine, while the prevention group received BAC (2 mg/kg, i.p.) before NAL. Thirty minutes after NAL, animals were sacrificed by transcardial perfusion. Brains were removed and slices were obtained to perform immunohistochemical studies. Our results show a significant decrease in c-Fos expression in hippocampal dentate gyrus, CA3, and CA1 areas of morphine withdrawn males, vs. their control group. Conversely, in females, the number of c-Fos positive nuclei was not modified in any of the areas studied. BAC pretreatment had no effect on the decreased c-Fos expression in morphine withdrawn males. The sexual dimorphism observed here confirms the greater sensitivity of males over females in their response to morphine. The preventive action of BAC on the expression of morphine withdrawal would not be related to an effect on c-Fos expression.